Análise dos fatores de risco para pneumonia nosocomial em pacientes politraumatizados de um hospital terciário - Pilicie, Lorena Ferreira (2016)
Introduction: Nosocomial pneumonia is among the main respiratory complications in polytrauma patients. Identifying the risks early to the development of this infection contributes to the optimization of the initial management of these patients, however, the mechanisms involved in the development of the infection in polytrauma patients remain in question. Objective: To identify the potential risk factors for the development of nosocomial pneumonia in polytrauma patients admitted to a tertiary hospital. Methods: A longitudinal and retrospective study was carried out in which records of patients hospitalized for a period longer than 48 hours were analyzed at the Clinics Hospital of the Federal University of Uberlândia and were admitted with polytrauma. The variables analyzed in the medical records were related to demographic data, antecedents, admission and trauma data, hospitalization data, invasive hospital procedures, presence of pneumonia during hospitalization and criteria used to define the infection. Results: We analyzed 70 patients with polytrauma diagnosis. There was pneumonia in 15 patients (21.4%) with predominance up to the fifth day of hospitalization. The results in the univariate logistic regression model showed that the Glasgow Coma Scale at admission (p = 0.03), endotracheal tube (p = 0.01) and nasogastric tube (p = 0.04) were associated with the increased risk of nosocomial pneumonia in polytraumatized patients. In the multivariate analysis, the use of the endotracheal tube was considered an independent risk factor for the development of the infection. Conclusion: The study allowed us to demonstrate that in this population of polytrauma patients, the risk factors for the development of the infection were: lower values of the Glasgow Coma Scale at admission, nasogastric tube use and endotracheal tube use and were related both to procedures performed during The period of hospitalization for factors recorded at the time of admission.